My Big Dog - Stevens, Janet; Crummel, Susan Stevens (New York : Golden Books, 2005)
Merl the cat has a perfect home until the arrival of a puppy.
"Originally published in 1999 in slightly different form by Golden Books Publishing Company, Inc."
Keywords: Cats -- Fiction; Dogs -- Fiction; Friendship -- Fiction; Picture book